2022-RA-1090-ESGO Descriptive study of vulvar cancers according to the vulnerability of patients related to age: multicenter study. (20th October 2022) - Raimond, Emilie; Ambroise, Caroline; Mimoun, Camille; Kerbage, Yohan; Ouldamer, Lobna; Bendifallah, Sofiane; Carcopino, Xavier; Koskas, Martin; Bolze, Pierre Adrien; Lavoue, Vincent; Gauthier, Tristan; Graesslin, Olivier; et al.
Abstract : Introduction/Background: The purpose of this study is to assess the impact of age on tumor size in vulvar cancer. Methodology: This is a multicenter retrospective observational study incorporating 447 cases of vulva cancer. A limit age of 65 years was chosen to define the 2 groups of patients to compare. Results: Patients of <65 years more often had an induced HPV cancer history (16.1% (n=27) versus 3.9% (n=11), p <0.001), mainly history of uterus cervical cancer. The location of tumors was also different between the 2 groups. The median clinical and post-operative size of the tumors was 20 mm (1–120) and 26 mm (1–65) in the group of patients under 65 and 30 mm (1–100) and 35 mm (1–66) in patients of> 65 years (p = 0.07 and p = 0.001, respectively). There was no difference concerning the in sano excision between the 2 groups. Multivariate analysis found that age> 65 years (p = 0.02) and a history of cervical cancer (p = 0.01) was greater post-operative risk factors of tumor. Conclusion: Age is a larger tumor size risk factor. In elderly and vulnerable women this can cause post-operative complications altering the quality of life of patients. It is therefore necessary to take into account the vulnerability linked to the age of patients in the overall management of vulvar cancers.